Burden of paediatric Rotavirus Gastroenteritis (RVGE) and potential benefits of a universal Rotavirus vaccination programme with a pentavalent vaccine in Spain - Diez-Domingo Javier; Suriñach Nuria; Alcalde Natalia; Betegón Lourdes; Largeron Nathalie; Trichard Mélanie (BMC, 2010)
Abstract Background Rotavirus is the most common cause of gastroenteritis in young children worldwide. The aim of the study was to assess the health outcomes and the economic impact of a universal rotavirus vaccination programme with RotaTeq, the pentavalent rotavirus vaccine, versus no vaccination programme in Spain. Methods A birth cohort was followed up to the age of 5 using a cohort model. Epidemiological parameters were taken from the REVEAL study (a prospective epidemiological study conducted in Spain, 2004-2005) and from the literature. Direct and indirect costs were assessed from the national healthcare payer and societal perspectives by combining health care resource utilisation collected in REVEAL study and unit costs from official sources. RotaTeq per protocol efficacy data was taken from a large worldwide rotavirus clinical trial (70,000 children). Health outcomes included home care cases, General Practioner (GP)/Paediatrician, emergency department visits, hospitalisations and nosocomial infections. Results The model estimates that the introduction of a universal rotavirus vaccination programme with RotaTeq (90% coverage rate) would reduce the rotavirus gastroenteritis (RVGE) burden by 75% in Spain; 53,692 home care cases, 35,187 GP/Paediatrician visits, 34,287 emergency department visits, 10,987 hospitalisations and 2,053 nosocomial infections would be avoided. The introduction of RotaTeq would avoid about 76% of RVGE-related costs from both perspectives: €22 million from the national health system perspective and €38 million from the societal perspective. Conclusions A rotavirus vaccination programme with RotaTeq would reduce significantly the important medical and economic burden of RVGE in Spain.